Chemical etching to regulation oxygen vacancies on Mn-Fe PBA for highly efficient degradation of bisphenol A and acetaminophen. (1st December 2022) - Xu, Mingjun; Zhang, Qian; Zhu, Ziqi; Xue, Yuwei; Zhang, Ting; Hong, Junming
Abstract: Prussian blue analogs (PBAs) have been widely explored as catalyst for peroxymonosulfate (PMS) activation. However, the drawbacks of poor electron transfer ability and degradation performance of PBAs hinder their practical application. In this study, oxygen vacancy (OV)-rich Mn-Fe PBA was regulated through phosphoric acid and ammonia water chemical etching to overcome these drawbacks. Experimental and theoretical investigations indicated that the regulation of OVs was favorable for more Fe 2+ and Mn 3+ active sites exposure and higher specific surface area to facilitate PMS activation. Sulfate radical (SO4 − ), hydroxyl radical (HO), and single oxygen ( 1 O2 ) were verified as main reactive species for PMS activation during catalytic reaction. Density functional theory calculation results showed that the OV-rich NOE-PC-300 had the highest pollutants degradation capability, with complete degradation of bisphenol A (BPA) and acetaminophen (APAP) within 40 min. Through regulation of OVs by chemical etching, highlighted adsorption ability and elongated O–O bond of PMS were obtained. This research showed that NOE-PC-300 is an efficient and harmless catalyst for activating PMS, and it has immense application potential in practical wastewater treatment. Graphical abstract: Image 1 Highlights: Regulation of Mn-Fe PBA oxygen vacancy content by different etchants. Through regulation of OVs by chemical etching, facilitates the peroxymonosulfate adsorption. Simultaneous study on the degradation mechanism of pollutants with single benzene ring and polyphenyl ring structure.